Resilience in Cancer Patients - Seiler, Annina; Jenewein, Josef (Frontiers in Psychiatry, 2019)
Background: Being diagnosed with cancer and undergoing its treatment are associated with substantial distress that can cause long-lasting negative psychological outcomes. Resilience is an individual’s ability to maintain or restore relatively-stable psychological and physical functioning in the face of stress and adversities. Posttraumatic growth (PTG) is characterized by positive life changes resulting from major life crises or stressful events. Objectives: (1) to investigate which factors can strengthen or weaken resilience and PTG in cancer patients and survivors; (2) to explore the relationship between resilience and PTG, and mental health outcomes; and (3) to discuss the impact and clinical implications of resilience and PTG on the process of recovery from cancer. Methods: A literature search was conducted, restricted to PubMed through May 2018, utilizing the following key words: cancer, cancer patients, cancer survivors, resilience, posttraumatic growth, coping, social support, and distress. Results: Biological, personal, and most importantly social factors contribute to cancer patients’ resilience and, consequently, to favorable psychological and treatment-related outcomes. PTG is an important phenomenon in the adjustment to cancer. From the literature included in this review, a model of resilience and PTG in cancer patients and survivors was designed. Conclusions: The cancer experience is associated with positive and negative life changes. Resilience and PTG are quantifiable and can be modified through psychological and pharmacological interventions. Promoting resilience and PTG should be a critical component of cancer care.